If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + 36 = 5m Reorder the terms: 36 + m = 5m Solving 36 + m = 5m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-5m' to each side of the equation. 36 + m + -5m = 5m + -5m Combine like terms: m + -5m = -4m 36 + -4m = 5m + -5m Combine like terms: 5m + -5m = 0 36 + -4m = 0 Add '-36' to each side of the equation. 36 + -36 + -4m = 0 + -36 Combine like terms: 36 + -36 = 0 0 + -4m = 0 + -36 -4m = 0 + -36 Combine like terms: 0 + -36 = -36 -4m = -36 Divide each side by '-4'. m = 9 Simplifying m = 9
| 18.3+x= | | .10x+.25y=2.75 | | 3x-(-2-4x)x=5 | | 7(3x+2)=77 | | -2y(y+6)=y+3+2y | | -3.2+14z=15z | | 24=y/6 | | -3x+(2+4x)x=5 | | 8p-7=0 | | .4y-8=.4y+16 | | 8.1s-9=7.1s-9 | | 1-(-7)=-6 | | 3x+(2+4x)x=5 | | 12-4n=2 | | -3a+b=5ac | | 34-8=35-x | | 6w^2-5w-4=0 | | 3x+(5x+10)+3x+(5x+10)=165 | | 2x+4=-1x+7 | | y=112(x-7)+10 | | 0.02x=0.82 | | -3*5=-15 | | 9x-8=76-3x | | 3x^3-4x^2-5x=0 | | -5=-6+w | | 9x-3x=76-3x | | Z+23=41 | | 2=6-4n | | 3x-(5-4x)=7x+3 | | 6=6-4n | | 0.5x+x+8=23 | | 8/11*3/2-1/2 |